Synergistic Action of a Microbial-based Biostimulant and a Plant Derived-Protein Hydrolysate Enhances Lettuce Tolerance to Alkalinity and Salinity - Rouphael, Youssef; Cardarelli, Mariateresa; Bonini, Paolo; Colla, Giuseppe (Frontiers in Plant Science, 2017)
In the coming years, farmers will have to deal with growing crops under suboptimal conditions dictated by global climate changes. The application of plant biostimulants such as beneficial microorganisms and plant-derived protein hydrolysates (PHs) may represent an interesting approach for increasing crop tolerance to alkalinity and salinity. The current research aimed at elucidating the agronomical, physiological, and biochemical effects as well as the changes in mineral composition of greenhouse lettuce (Lactuca sativa L.) either untreated or treated with a microbial-based biostimulant (Tablet) containing Rhizophagus intraradices and Trichoderma atroviride alone or in combination with a PH. Plants were sprayed with PH at weekly intervals with a solution containing 2.5 ml L-1 of PH. Lettuce plants were grown in sand culture and supplied with three nutrient solutions: standard, saline (25 mM NaCl) or alkaline (10 mM NaHCO3 + 0.5 g l-1 CaCO3; pH 8.1). Salt stress triggered a decrease in fresh yield, biomass production, SPAD index, chlorophyll fluorescence, leaf mineral composition and increased leaf proline concentration, without altering antioxidant enzyme activities. The decrease in marketable yield and biomass production under alkali stress was not significant. Irrespective of nutrient solution, the application of Tablet and especially Tablet + PH increased fresh marketable yield, shoot and root dry weight. This was associated with an improvement in SPAD index, Fv/Fm ratio, CAT and GPX activities and a better nutritional status (higher P, K and Fe and lower Na with NaCl and higher P and Fe with NaHCO3) via an increase of total root length and surface. The combination of microbial biostimulant with foliar application of PH synergistically increased the marketable fresh yield by 15.5% and 46.7% compared to the Tablet-treated and untreated plants, respectively. The improved crop performance of Tablet + PH application was attributed to a better root system architecture (higher total root length and surface), an improved chlorophyll synthesis and an increase in proline accumulation. Combined application of Tablet and PH could represent an effective strategy to minimize alkalinity and salinity stress in a sustainable way.